2023
DOI: 10.1002/ejic.202300213
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Mn‐Mg‐Al Mixed Oxides Composition on their Activity towards the Total Oxidation of Aromatic and Oxygenated VOCs

Abstract: A series of mixed oxides (Mn-Mg-Al) is prepared by coprecipitation via a hydrotalcite route with different manganese ratios. Structural, textural, and redox properties are studied by XRD, N 2 -sorption, H 2 -TPR, and XPS techniques. Mn x Mg 6-x Al 2 -O mixed oxides (with 0 � x � 6) are tested in the total oxidation of ethanol and toluene, two probe molecules representing respectively oxygenated and aromatic VOCs. Catalysts with higher manganese contents have shown the best catalytic performance for the oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
2
3
0
Order By: Relevance
“…First of all, the reduction profile of all samples showed some similar behavior, with two reduction steps: the first one at low temperature (T < 400 °C), corresponding to a reduction in the Co3O4 phase to Co 0 , and the second one at higher temperature, with a reduction in Co-Al spinel phases (CoAl2O4 and Co2AlO4). This reduction is well documented in the literature [14,[26][27][28][29][30]. Concerning the gold-based catalysts, it was observed that the 1Au/CoAl HT (A) showed the first reduction zone at higher temperature compared to the Au/CoAl HT (B) samples, while the presence of gold did not influence the position of the second peak, which remained centered at around 750 °C.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…First of all, the reduction profile of all samples showed some similar behavior, with two reduction steps: the first one at low temperature (T < 400 °C), corresponding to a reduction in the Co3O4 phase to Co 0 , and the second one at higher temperature, with a reduction in Co-Al spinel phases (CoAl2O4 and Co2AlO4). This reduction is well documented in the literature [14,[26][27][28][29][30]. Concerning the gold-based catalysts, it was observed that the 1Au/CoAl HT (A) showed the first reduction zone at higher temperature compared to the Au/CoAl HT (B) samples, while the presence of gold did not influence the position of the second peak, which remained centered at around 750 °C.…”
Section: Resultssupporting
confidence: 84%
“…Looking at the hydrogen consumption (Table 2), it is worth noting that the 1Au/CoAl HT (A) exhibited the highest values for both peaks at both low and high temperature, whereas the hydrogen consumed by all the catalysts prepared with method (B) was the First of all, the reduction profile of all samples showed some similar behavior, with two reduction steps: the first one at low temperature (T < 400 • C), corresponding to a reduction in the Co 3 O 4 phase to Co 0 , and the second one at higher temperature, with a reduction in Co-Al spinel phases (CoAl 2 O 4 and Co 2 AlO 4 ). This reduction is well documented in the literature [14,[26][27][28][29][30]. Concerning the gold-based catalysts, it was observed that the 1Au/CoAl HT (A) showed the first reduction zone at higher temperature compared to the Au/CoAl HT (B) samples, while the presence of gold did not influence the position of the second peak, which remained centered at around 750 • C. The reduction in the active Co 3 O 4 phase at lower temperature for Au catalysts prepared with method (B) can be explained by the strong interaction between Au nanoparticles and Co 3 O 4 species [31][32][33].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…At around 210 • C, the conversion of EA reached nearly 100% for the activation of abundant oxygen vacancies. Moreover, it has been discovered that the synergistic effects of composite oxides contribute to the significant enhancement of catalytic activities, such as Cu-Mn-O [17], Co-Mn-O [18], Ni-Mn-O [19] and Mg-Mn-O [20]. Due to its lower working temperature and higher selectivity to CO 2 , catalytic ozonation has become one of the popular methods for VOC degradation in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in our recent work [21], we tested the ethanol oxidation over Mn x Mg (6−x) Al 2 -O (x = 0-6) catalysts obtained by LDH thermal decomposition. It was established that the ethanol transformation was influenced by the metal ratio, and the Mn 4 Mg 2 Al 2 -O catalyst exhibited superior activity compared to the supported metal Pd/γ-Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%